The Interplay of Workload and Motivation in Predicting Burnout Among Healthcare Workers in Tourism-Based Clinics - Jeffrey Ariesta Putra; Sylvia Diana Purba (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
Increasing service demands in tourism-based health facilities heighten the risk of burnout among healthcare workers. This study investigated the effects of workload and work motivation on burnout among healthcare workers in tourism-based clinics in Indonesia, focusing on emotional exhaustion, depersonalization, and personal accomplishment. A cross-sectional analytical design was applied to 124 doctors and nurses within the Klinik OMSA Medic Bali network. Workload was assessed using NASA-TLX, motivation with the Nursalam Motivation Scale, and burnout with the Maslach Burnout Inventory. Data analysis included descriptive statistics, Pearson correlations, multiple linear regression, and mediation testing using Hayes PROCESS Model 4 with 5,000 bootstrap samples. Emotional Exhaustion was the most prevalent burnout dimension. Results showed that workload significantly predicted higher levels of emotional exhaustion and depersonalization. Work motivation was significantly associated with lower emotional exhaustion and depersonalization and higher personal accomplishment, indicating a protective role. However, motivation did not mediate the relationship between workload and any burnout dimension, as indirect effects were not significant. Workload emerged as the main contributor to burnout, while motivation functioned as a supportive but non-mediating factor. Organizational strategies aimed at workload management and motivation enhancement are recommended to reduce burnout and sustain healthcare service quality.